An integrated method of identifying and ranking danger spots for pedestrians on microlocation - Pešić, Dalibor; Vujanić, Milan; Lipovac, Krsto; Antić, Boris (Transport, 2012)
In traffic safety, various methods, procedures and techniques are adapted for traffic safety needs. Diverse methods lead to a different degree of exactness, accuracy and precision. The selection of research methods depends primarily on the research objective. Research methods most frequently applied for traffic safety include a statistical method, experiment, observation, tests, a questionnaire and interview, a comparison and analogy, etc. Each method has its advantages and disadvantages; however, a well devised combination of several methods and the reliability of research results can be increased. The problem of danger for pedestrians, as vulnerable road users, is constantly expressed and present in all regions. Therefore, special attention should be paid to pedestrian safety. To determine danger spots for pedestrians, the analyses of traffic accidents are most frequently used, which is the so called reactive approach to traffic safety improvement. Apart from the reactive approach, for the purpose of preventing traffic accidents in the future, it is necessary to combine some of the methods that can proactively indicate potential danger spots for pedestrians. This paper shows the method of identifying and ranking danger spots for pedestrians on micro locations, which incorporates the analysis of traffic accidents, the examination of the subjective attitudes of participants in traffic and the use of a conflict technique. Along with the so called ‘overlapping’ danger spots detected in the analysis of traffic accidents, danger spots detected based on the analysis of the subjective attitudes of pedestrians and drivers and danger spots detected in the conflict technique, a map of the so called objective and subjective danger spots is obtained. By eliminating all such identified danger spots, black spots as well as potential traffic accidents are removed. The method presented in this paper can be a very useful tool for decision-makers, for improving pedestrian safety on a micro location and for allocating funds.First Published Online: 30 Mar 2012